The Involvement of Ethnic Minorities in the Administration of the LSSR and the Ethnic Relations in Soviet Bureaucracy between 1940 and 1941 - Maslauskienė, Nijolė (Genocidas ir rezistencija, 2001)
Having annexed Lithuania, the Soviet Union destroyed the country’s independence, and formed its own administrative unit the Lithuanian Soviet Socialist Republic – on the territory of the former independent Lithuanian republic. The Soviets imposed their own political system, created a mechanism for the administration of the annexed country and formed local governments. In seeking to involve minority ethnic groups in the process of the Sovietization of annexed Lithuania in order to implement the policies of the Communist (Bolshevik) Party and to form a multinational group of local administrators, the Communist Party used communists and their supporters. Since the Lithuanians were opposed to the occupying regime, the Soviets were not able to trust them and had to rely on minority ethnic groups. Attempts were made to strengthen their role in the administrative bodies, and to counterbalance their numbers against Lithuanians. Seeking to strengthen its power in the Vilnius region and to isolate the Polish groups, which had hoped that after the war the Vilnius region would be transferred to Poland, the Soviet Union strove to weaken the influence of Poles in the region’s administration, in particular in Vilnius. At the outbreak of the Second World War part of the Jewish community were geopolitically oriented towards the USSR, and left-wing Jewish groups took an active part in the communist movement: the Soviet Communist Party created conditions for Jews to get involved in the administration of the LSSR, and they received most support from the Soviets. This section of the Jewish community was involved in the administrative bodies of the LSSR thanks to the occupying regime and the initiative of the communists. and their position was directly dependent on the stability of the regime. Some functionaries of the former independent country who remained to work in offices of the LSSR and communists of various nationalities (and people chosen by them) who were employed in the administration of the LSSR were polarized due to their political interests and objectives. Communists and those they supported were united by the policy of the Communist (Bolshevik) Party. Ethnic minorities strove to strengthen their own influence in the administration of the LSSR, which increased ethnic tensions, further strengthened by the national and cadre policy being implemented in Lithuania by the Communist Party. The tensions between various bureaucratic groups exerted an influence on society and formed an atmosphere of racism and intolerance.